2019
DOI: 10.33594/000000152
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal HSP90 Inhibitors Block the HIF-1 Hypoxic Response by Degrading HIF-1α through the Oxygen-Dependent Degradation Pathway

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…It has been widely reported that low oxygenation, which arises as a consequence of imbalance between the oxygen supply and oxygen consumption, is a hallmark of solid tumors [ 43 ]. HIF-1α is a crucial regulator of oxygen homeostasis, and its transcription is modulated by Hsp90 expression [ 44 ]. As a chaperone, Hsp90 is the most abundant protein in the cytosol, and HSP90 interacts with HIF-1α and inhibits HIF-1α ubiquitination, ultimately leading to HIF-1α stabilization, which is correlated with tumorigenesis and progression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that low oxygenation, which arises as a consequence of imbalance between the oxygen supply and oxygen consumption, is a hallmark of solid tumors [ 43 ]. HIF-1α is a crucial regulator of oxygen homeostasis, and its transcription is modulated by Hsp90 expression [ 44 ]. As a chaperone, Hsp90 is the most abundant protein in the cytosol, and HSP90 interacts with HIF-1α and inhibits HIF-1α ubiquitination, ultimately leading to HIF-1α stabilization, which is correlated with tumorigenesis and progression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDACi contributes to hyperacetylation of HSP90 with the repression of chaperone function, leading to the accumulation and vigorous degradation of immature HIF-1α mediated by pVHL [21]. In contrast, the research of Kataria et al [35] revealed that by targeting the ATPbinding pocket at the N-terminus of HSP90, HSP90 disassociates with HIF-1α, prompting the pVHL-independent degradation of HIF-1α. Therefore, we examine expression level of pVHL to determine whether pVHL directly mediates degradation of HIF-1α upon HDAC inhibition.…”
Section: Hdaci-induced Pvhl Independent Degradation Of Hif-1αmentioning
confidence: 98%
“…HSP90 promotes rapid accumulation of HIF-1α through the direct interaction with PAS domain of HIF-1α, thereby inducing structural change of HIF-1 heterodimer and stabilizing HIF-1α against pVHL-independent degradation [20,63]. Kataria et al [35] revealed that via inhibiting C-terminus of HSP90, proteasome degradation of HIF-1α would be initiated via PHD, even in hypoxia. Another subset of chaperone family member HSP70, is the cytosolic substrate of HDAC5 and HDACiinduced hyperacetylation renders HSP70 a higher affinity to HIF-1α, leading to the accelerated degradation and attenuated nuclear accumulation of HIF-1α [37].…”
Section: Plos Onementioning
confidence: 99%
“…prolongs the half-life of the E2F1 protein by inhibiting its ubiquitination (MDM2 displaces SCFSKP2); influences cell proliferation [168] MYCBP2 Atypical E3 ubiquitin-protein ligase, which mediates ubiquitination of threonine and serine, instead of lysine residues AR, MYC [138] Tumorigenicity of AR-positive PCa cells [138] MYLIP E3 ubiquitin-protein ligase whose activity depends on E2 enzymes of the UBE2D family AR [172] AR activity [172] PIRH2 Ring finger protein with ubiquitin ligase activity Epsilon-COP [173]; HDAC1 [174] Regulation of the secretion of PSA [173]; AR signaling [174] pVHL Substrate recognition subunit of the VHL-Elongin B/C E3 ligase complex that targets the HIF-1/2 for proteasomal degradation under normoxia conditions AR (enhanced AR de-ubiquitination instead of inducing AR ubiquitination) [175]; HIF-1α [176] Suppression of AR activity [175]; HIF-1 hypoxic response [176] RNF2 Also known as RING1b or RING2; catalytic subunit of PRC1 TXNIP [177]; CCL2 [178] Cell cycle arrest and apoptosis [177]; metastasis in mice inoculated intracardially with PC-3M cells [178]…”
Section: Mdm2mentioning
confidence: 99%